Book Reviews. Issue 1 (1st March 2021) - Unknown
Abstract : Ewa Stańczyk, ed., Comic Books, Graphic Novels and the Holocaust: Beyond Maus. (Abingdon and New York: Routledge, 2020). 142 pp. ISBN: 9780367585921 (£29.59) Vittorio Frigerio, Bande dessinée et littérature: Intersections, fascinations, divergences (Macerata: Quodlibet, 2018). 96 pp. ISBN: 9788822902573 (€10.00)